The Impact of Prenatal Nutritional Status on Occlusion of Primary Teeth among Kindergarten Childrenin Al- Kut City/ Wassit - Wathba Mohammed Jabber1, Ban Sahib Diab2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: When malnutrition begins early in life it affects adversely various aspects of growth including dental arch and increase the severity of oral problems in later life. The aim of present study was to assess the effect of prenatal malnutrition on the occlusion of primary teethMaterial and method: This survey was conducted among urban kindergarten children in Al- Kut city of Wasitt governorate. The sample959 children aged 4 and 5 years were randomly selected from different areas of Al-kut city. The assessment of nutritional status was performed using prenatal anthropometric measurements,and primary dentition terminus was used for assessing dental arch relation.Result: According to prenatal anthropometric indices preterm children constitute 23.46%, whereas low birth weight children constitute 13.66%. Flush terminus plane was the more prevalent type of occlusion for the total sample 47.86% while among preterm and low birth weighted children the mesial step terminus was more prevalent type of occlusion.Conclusion: The prenatal mal nutrion had some effect on the arch relation among kindergarten children.